Protonation Pattern, Tautomerism, Conformerism, and Physicochemical Analysis in New Crystal Forms of the Antibiotic Doxycycline - Santos, Olimpia M. M.; Silva, Douglas M.; Martins, Felipe T.; Legendre, Alexandre de Oliveira [UNESP]; Azarias, Lilian C.; Rosa, Iara M. L.; Neves, Person P.; Araujo, Magali B. de; Doriguetto, Antonio C. (Amer Chemical Soc, 2014)
Doxycycline (DOX) is a tetracycline class drug that is used worldwide as a broad-spectrum antibiotic. Although its clinical importance and use have been known since the 1960s, only four crystal forms have been reported until now. These are doxycycline hyclate (DOX center dot HYC), which is a hydrochloride salt hemiethanolate-hemihydrate; its isomorphous hydrobromide, hydrochloride salt dihydrate (DOX center dot HCl center dot 2H(2)O); and doxycycline monohydrate (DOX center dot H2O). Here we report the preparation of two new multicomponent molecular crystal forms of doxycycline and their crystal structure determination along with their melting temperature, aqueous solubility, and time-dependent dissolution profile. These crystal forms are a hydronitrate salt hemihydrate (DOX center dot HNO3 center dot 0.5H(2)O) and an acetic acid solvate dihydrate (DOX center dot HAc center dot 2H(2)O). The two new doxycycline crystal forms were compared with known forms, including DOX center dot HCl center dot 2H(2)O, the structure of which was redetermined in this work. The structural variability of the protonation patterns, tautomerism of the keto-enolate moieties, and conformation of the amide groups was observed for these compounds. While intramolecular rings assembled through resonance-assisted hydrogen bond (RAHB) were observed in both fused keto-enol moieties of all structures, DOX center dot HCl center dot 2H(2)O and DOX center dot HNO3 center dot 0.5H(2)O have another RAHB encompassing the protonated amide carbonyl oxygen and the enolate oxygen. These two crystal forms have a net positive charge on their drug molecule as DOX center dot HYC. They crystallize with the N,N-dimethylamine and amide carbonyl groups protonated and the neighboring hydroxyl group deprotonated. DOX, by contrast, crystallizes as a zwitterion in DOX center dot HAc center dot 2H(2)O similarly to DOX center dot H2O. Their amide carbonyl oxygens are not protonated, which differs from the salt forms. DOX center dot HNO3 center dot 0.5H(2)O presents as two tautomers that are similar to those of DOX center dot HYC, namely, T1, in which the enolate oxygen is next to the protonated amine group, and T2, with the carbonyl oxygen close to the protonated amine group. These tautomers also differ in their amide conformations due to a rotation of ca. 180 degrees on the C-C bond axis of the amide group, which directs the protonated carbonyl oxygen toward the enolate oxygen. DOX center dot HCl center dot 2H(2)O has only one T1-like tautomer and therefore only one amide conformation similar to that of T1. A T1-like keto-enolate tautomer is present in DOX center dot HAc center dot 2H(2)O, which exhibits an amide conformation similar to that of T2. Thermal (DSC and TG) and infrared analysis and equilibrium solubility, dissolution profiles, and forced degradation studies were performed to both new and known DOX forms. The results were correlated with their structural features. DOX center dot HNO3 center dot 0.5H(2)O was the most soluble form. This new form was also more stable than the commercial DOX center dot HYC in the oxidation test and more stable than commercial DOX center dot H2O against acid and basic hydrolysis and in the photostability study. DOX center dot HNO3 center dot 0.5H(2)O and DOX center dot HYC (commercial form) were observed to have similar drug release behaviors from capsules (F2 > 50) and therefore they could be interchangeable.